PENGARUH JUMLAH ORANG YANG MELAKUKAN TEST PCR TERHADAP KENAIKAN KASUS POSITIF COVID-19 DENGAN METODE REGRESI LINEAR SEDERHANA - Alinda Putri, Salsabila (Jurnal Riset Informatika dan Teknologi Informasi, 2024)
In 2020, there was a lot of news broadcasting the existence of a new virus which we usually know as Covid-19. The WHO states that this virus can spread quickly through the air and face-to-face contact with other people. Therefore, the government urges the public to comply with the protocols that have been established and carry out health tests in the form of PCR tests or Rapid Tests to be able to identify whether the person is affected by the virus or not, but many people also doubt whether the test is accurate or just a formality. Therefore, the author conducted this research to determine whether there is a strong relationship or influence between people who carry out PCR tests on the increase in positive cases of Covid-19. To determine whether there is a strong influence between variable one (PCR test) and variable two (positive Covid ) then the author uses a simple linear regression method in the calculation process.